2020
DOI: 10.1097/md.0000000000021730
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal aorta calcification predicts cardiovascular but not non-cardiovascular outcome in patients receiving peritoneal dialysis

Abstract: Abdominal aorta calcification (AAC) is associated with worse clinical outcomes in dialysis patients. However, the long-term prognostic values of AAC to cardiovascular (CV) and non-CV mortality in patients starting peritoneal dialysis (PD) remain unknown. This study is aimed to the analyze the predictive power of AAC to CV and non-CV mortality in PD patients. We prospectively enrolled 123 patients undergoing PD. All patients received quantitative analysis of AAC via abdominal computer tomography at enrollment. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Vascular calcification is another important risk factor for cardiovascular mortality in patients on PD [ 33 ]. In patients with chronic kidney disease, vascular calcification is characterized by medial arterial calcification [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular calcification is another important risk factor for cardiovascular mortality in patients on PD [ 33 ]. In patients with chronic kidney disease, vascular calcification is characterized by medial arterial calcification [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results from the 11 selected studies (Table 1) revealed a diverse landscape of measurement methods for calcifications in the aorto-iliac arteries. Seven studies adopted manual measurement techniques [10,11,[14][15][16]18,19], while the remaining studies explored automatic methods leveraging advanced technologies [12,13,17,20].…”
Section: Calcification Measurement Methodsmentioning
confidence: 99%
“…The calcification index was calculated as the mean value of the percentage for the 10 slices. A similar method was applied in the study of Tsai et al [11], where the calcified index was measured by the standard 64-multiple detector CT (MDCT) scan (LightSpeed VCT, GE Healthcare, Milwaukee, WI). The calcified area was calculated based on an attenuation range of >150 Hounsfield Units (HU) using image analysis software.…”
Section: Manual Measurement Methodsmentioning
confidence: 99%
“…Adeney et al demonstrated that even in patients with moderately advanced CKD (eGFR < 60 mL/min per 1.73 m 2 , mean 50.6 mL/min per 1.73 m 2 ) Shanahan without symptomatic cardiovascular disease (CVD), but with high serum phosphate level the prevalence and advancement of coronary artery calcification (CAC), calcification of descending aorta and mitral valve were significantly more pronounced as compared to subjects with normal kidney function [ 7 ]. Several studies reported the association between the risk of CV events and CV death and the degree of VC identified in several locations (coronary arteries, aortic arch and abdominal aorta) in different CKD patient groups (peritoneal dialysis, hemodialysis and pre-dialysis) [ 8 , 9 , 10 ]. The risk of cardiovascular and cerebrovascular events attributed to VC is largely independent from “traditional” risk factors for development of atherosclerosis, such as smoking, obesity or serum LDL-cholesterol [ 11 , 12 , 13 , 14 ].…”
Section: Introduction: Pathologic Calcification In Cardiovascular Systemmentioning
confidence: 99%